Wittenbergben vásárolt Kálvin-kötetekről – Kísérlet a peregrináció-kutatás továbbfejlesztésére - Ősz, Sándor (Gerundium, 2017)
On Calvin Volumes bought in Wittenberg. An Experiment for Improvement of the Peregrination Research. This paper represents a further step towards the exploitation and extension of the current achievements related to the research of peregrination with the help of Book History. The main focus is on those volumes of John Calvin, which were bought by Hungarian or Transylvanian students in Wittenberg during the 16th century and in present they are being located in Transylvanian collections. Analyzing the dates of the acquisitions it is revealed that during the 1570’s 32 volumes got to inland owners. This represents 15% of the records being available to our disposal, and one third of the volumes of John Calvin arriving in the 16th century. About 60% of the owners are Transylvanian Saxons. Their purchase of books reflects on the one hand the crypto-Calvinist-Melanchtonian intellectuality at the University of Wittenberg before 1575, and the theological disputes present at the church of the Transylvanian Saxons on the other.